The earliest diverging extant scleractinian corals recovered by mitochondrial genomes - Seiblitz, Isabela G. L.; Capel, Kátia C. C.; Stolarski, Jarosław; Quek, Zheng Bin Randolph; Huang, Danwei; Kitahara, Marcelo V. (Scientific Reports, 2020)
Evolutionary reconstructions of scleractinian corals have a discrepant proportion of zooxanthellate reef-building species in relation to their azooxanthellate deep-sea counterparts. In particular, the earliest diverging “Basal” lineage remains poorly studied compared to “Robust” and “Complex” corals. The lack of data from corals other than reef-building species impairs a broader understanding of scleractinian evolution. Here, based on complete mitogenomes, the early onset of azooxanthellate corals is explored focusing on one of the most morphologically distinct families, Micrabaciidae. Sequenced on both Illumina and Sanger platforms, mitogenomes of four micrabaciids range from 19,048 to 19,542 bp and have gene content and order similar to the majority of scleractinians. Phylogenies containing all mitochondrial genes confirm the monophyly of Micrabaciidae as a sister group to the rest of Scleractinia. This topology not only corroborates the hypothesis of a solitary and azooxanthellate ancestor for the order, but also agrees with the unique skeletal microstructure previously found in the family. Moreover, the early-diverging position of micrabaciids followed by gardineriids reinforces the previously observed macromorphological similarities between micrabaciids and Corallimorpharia as well as its microstructural differences with Gardineriidae. The fact that both families share features with family Kilbuchophylliidae ultimately points towards a Middle Ordovician origin for Scleractinia.